Duration of Surgery, Ventilation, and Length of Hospital Stay Do Not Affect Breastfeeding in Newborns After Early Cleft Lip Repair - Burianova, Iva; Cerny, Milos; Borsky, Jiri; Zilinska, Kristyna; Dornakova, Jana; Martin, Aisling; Janota, Jan (The Cleft palate-craniofacial journal, 2021)
OBJECTIVE: There are minimal data available on nutrition after early repair of cleft lip and the factors influencing initiation of breastfeeding. This study assessed the impact of the length of surgery, length of ventilation support, and duration of hospital stay on breastfeeding rates after early cleft lip surgery. DESIGN: This is a prospective observational cohort study comparing 2 hospitals providing early surgical repair of facial clefts from January 2014 to December 2016. Both hospitals are designated as Baby-Friendly Hospitals. Demographic and anthropometric data from mothers and newborns were recorded. SETTING: Tertiary neonatal and pediatric surgery center. PATIENTS: Hospital A: 61 newborns, Hospital B: 157 newborns. INTERVENTIONS: Early (day 5 to 14) cheiloplasty in newborns with cleft lip or cleft lip and palate. MAIN OUTCOME MEASURES: Influence of duration of hospital stay, length of operation, and artificial ventilation on the rate of breastfeeding. RESULTS: Significantly, more newborns were breastfed following early surgical repair of an isolated cleft lip compared to those with both cleft lip and palate, in both hospitals (hospital A 82% vs 0%, P = .0001, hospital B 66% vs 5%, P = .0001). Duration of hospital stay, length of operation, and duration of artificial ventilation did not significantly affect the rate of breastfeeding. CONCLUSIONS: The factors associated with early cleft lip repair (length of operation, length of ventilation support, and duration of hospital stay) do not affect breastfeeding rate.
Keywords: Cleft Palate; Female; Cleft Lip; Infant; dítě; novorozenec; ženské pohlaví; lidé; early surgery; Infant, Newborn; rozštěp patra; délka pobytu; cleft lip; Length of Stay; rozštěp rtu; prospektivní studie; kojenec; Breast Feeding; Prospective Studies; nutrition; breastfeeding; Child; kojení; Humans